Adsorption of Isonicotinamide on Loughlinite (Natural Na-Sepiolite): An FT-IR Spectroscopic Study - AKYÜZ, ZEKİ TANIL; AKYÜZ, SEVİM (Asian Journal Of Chemistry, 11/100 Rajendra Nagar, Sector 3, Sahibabad 201 005, Ghaziabad, India, 2014)
In this study adsorption of isonicotinamide on loughlinite (Na-sepiolite) has been investigated by FT-IR spectroscopy. The adsorption of isonicotinamide showed a considerable alteration on both Si-OH stretching and deformation peaks of loughlinite structure. Spectroscopic results indicate that adsorbed isonicotinamide molecules onto loughlinite are coordinated to surface silanol groups and/or Lewis acidic centers by H-bonding interaction through pyridine ring nitrogen lone pairs. The amino nitrogen is found to be relatively in active to adsorbing sites.
Keywords: Adsorption; Clays; IR spectroscopy; Isonicotinamide; Loughlinite; Sepiolite; Halide-Complexes; Montmorillonite; Picolinamide; Nicotinamide; Intercalation; Anatolia